Design and application of a multifunctional vented needle (一种多功能排气针的设计与应用) - WANG Li (王俐); LI Xinli (李昕砾); TAN Xiangyan (谭香燕) (中西医结合护理, 2024)
This paper introduces a multifunctional vented needle that can be used as a venting needle for infusion bottles, as a convenient and pollution-free mouthwash straw, and as a drinking straw under limited conditions. The innovation of this design lies in the application of the three-way mode and the end-break design of the tube body, which is convenient for patients to use and not easily contaminated, reducing the risk of infection for patients. The design structure includes a needle body, a three-way tube, a filter, and a protective cap. This design has the characteristics of multiple functions, strong clinical practicality, and low cost. (排气针是临床常用工具, 其可作为漱口工具使用。本研究介绍一种多功能排气针, 既能作为输液瓶排气针, 又能作为漱口水吸管, 同时还可以在条件有限的情况下用作饮水吸管。本设计创新地应用了三通结构连接三条管路, 通过旋转调节旋钮, 实现排气、漱口、饮水三个功能, 不仅具有较高的安全性、多功能实用性, 而且简化了护理工作流程, 有助于提高临床工作效率。)